2013
DOI: 10.4322/rbcv.2014.053
|View full text |Cite
|
Sign up to set email alerts
|

Perdas econômicas oriundas das condenações de vísceras bovinas em matadouros de Santa Maria, Rio Grande do Sul

Abstract: ResumoO objetivo deste trabalho foi mensurar as perdas causadas pela condenação de vísceras bovinas em matadouros sob fiscalização do Serviço de Inspeção Municipal (SIM) em Santa Maria, RS, durante 12 meses consecutivos. O estudo foi realizado através do levantamento de dados de quatro matadouros do município de Santa Maria, Rio Grande do Sul, Brasil, junto ao SIM. Os dados registrados foram o número de animais abatidos, número de órgãos condenados e principais lesões que levaram as condenações, no período de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 3 publications
1
3
0
11
Order By: Relevance
“…Prevalence of fasciolosis in this study was 37.6% (95% CI = 31.3-44.3), slightly over two-fold the value observed by Bennema et al (2014) in Rio Grande do Sul state, who reported prevalence of 14.39% in a sample of 8,427,727 cattle between 2002 and 2011, and closer to the value found by Fruet et al (2013), who described prevalence of 25.47% in the central region of the state with a sample of 9261 animals from 2010 to 2011. The high prevalence of fasciolosis compared with those of other causes of liver condemnation demonstrates the importance and economic impact that Fasciola hepatica can have on southern Rio Grande do Sul.…”
Section: Discussionsupporting
confidence: 75%
“…Prevalence of fasciolosis in this study was 37.6% (95% CI = 31.3-44.3), slightly over two-fold the value observed by Bennema et al (2014) in Rio Grande do Sul state, who reported prevalence of 14.39% in a sample of 8,427,727 cattle between 2002 and 2011, and closer to the value found by Fruet et al (2013), who described prevalence of 25.47% in the central region of the state with a sample of 9261 animals from 2010 to 2011. The high prevalence of fasciolosis compared with those of other causes of liver condemnation demonstrates the importance and economic impact that Fasciola hepatica can have on southern Rio Grande do Sul.…”
Section: Discussionsupporting
confidence: 75%
“…Carcasses and viscera are products resulting from the slaughter of bovine animals. Cattle slaughter by-products (viscera) add value to production, because they are of lower cost to consumers compared with other beef cuts, and serve as an alternative source of protein for the lower-income population worldwide (Kale et al 2011, Fruet et al 2013. Several pathologies can be diagnosed during slaughter, which may result in condemnation of carcasses and by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Israel et al (2014) reported that the lungs were the most doomed organs (36.10%), and then the kidneys (29.66%). Different result found Fruet et al (2013), in their researches, where the main organ condemned was the liver (40.46%), with a higher prevalence lesion due to Fasciola hepá tica.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 79%
“…ISSN 2166-0379 2019 The lungs and liver were the organs that generated greater economic losses (R$ 68,389.61) (Table 4). Fruet et al (2013) report a loss of R$ 87,108.05/year with organ condemnations. However, in the present study, the bovine carcasses, from which the highest value and income cuts occurred, had an economic loss of R$ 1,144,628.51, which is equivalent to 93.25% of the final loss.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%